Comparative study between supported and doped MgO catalysts in supercritical water gasification for hydrogen production. (5th February 2019) - Mastuli, Mohd Sufri; Kamarulzaman, Norlida; Kasim, Muhd Firdaus; Zainal, Zulkarnain; Matsumura, Yukihiko; Taufiq-Yap, Yun Hin
Abstract: Different catalyst structures may influence the catalytic performance of catalysts in supercritical water gasification (SCWG). This study reports the catalytic activity of supported (SP) and doped (DP) MgO catalysts in catalyzing the gasification of oil palm frond (OPF) biomass in supercritical water to produce hydrogen. Two types of supported catalysts, labelled as Ni-SP (nickel supported MgO) and Zn-SP (zinc supported MgO), were synthesized via impregnation method. Another two types of doped catalysts, labelled as Ni-DP (nickel doped MgO) and Zn-DP (zinc doped MgO), were synthesized by using the self-propagating combustion method. All the synthesized catalysts were found to be pure with the doped catalysts exhibited small crystallites, in comparison to that produced by the supported catalysts. The specific surface area increased in the order of Ni-DP (67.9 m 2  g −1 ) > Zn-DP (36.3 m 2  g −1 ) > Ni-SP (30.1 m 2  g −1 ) > Zn-SP (13.1 m 2  g −1 ). Regardless of supported or doped, the Ni-based catalysts always had larger specific surface area than that in the Zn-based catalysts. Unexpectedly, the Zn-based catalysts with smaller surface area for SCWG produced higher hydrogen (H2 ) yield from the OPF biomass. When compared to the non-catalytic reaction, the H2 yield increased by 187.2% for Ni-SP, 269.0% for Zn-SP, 361.7% for Ni-DP, and 438.1% for Zn-DP. Among the studied catalysts, the Zn-DP displayed the highest H2 yield because it had the highest number of basic sites; approximately twenty-fold higher than that of the Zn-SP catalyst. The Zn-DP also proved to be the most stable catalyst, as verified from the X-Ray photoelectron spectroscopy (XPS) results. As such, this study concludes that the catalytic performances of the synthesized catalysts do not only depend on the specific surface area, but they are also influenced by the number of basic sites and the catalyst stability. It is trustworthy to note that this is the initial study that associated SCWG with doped catalysts. The doped catalysts, hence, may serve as a new catalyst system to generate SCWG reactions. Graphical abstract: Highlights: Catalytic SCWG using supported and doped MgO catalysts. Doped catalysts exhibited interesting properties than the supported catalysts. Doped catalysts caused higher H2 yield than that of the supported catalysts. Doped catalysts are new promising catalysts for SCWG.